Makna Simbolik Verbal Dan Non-Verbal Pada Pasah Sahawung Di Desa Supang Kecamatan Kapuas Hulu Kabupaten Kapuas Provinsi Kalimantan Tengah Dan Implikasinya Terhadap Pembelajaran Bahasa Indonesia Di SMK - Arwo Arwo; Petrus Poerwadi; Patrisia Cuesdeyeni; Albertus Purwaka (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2026)
This study aims to describe the verbal symbols, non-verbal symbols, and the implications of the symbolic meaning of Pasah Sahawung on Indonesian language learning in vocational schools. The study uses a qualitative descriptive approach with Ferdinand de Saussure's semiotic theory. Data were obtained through observation, interviews, and documentation of traditional figures and Kaharingan religious leaders. Data analysis was carried out through data reduction, data presentation, and drawing conclusions based on the relationship between signifiers and signifieds. The results of the study indicate that the verbal symbols in Pasah Sahawung are incantations or ritual utterances that function as a medium of spiritual communication between humans and Ranying Hatala Langit. Non-verbal symbols are reflected in the seven-story building structure and ritual equipment that symbolize the cosmology of the Dayak Ngaju people, respect for ancestors, and the relationship between humans and the spiritual world. The results of the study can be implied in Indonesian language learning, especially the material of local wisdom-based observation report texts in vocational schools so as to improve cultural literacy, interpretative skills, and critical thinking of students.